Phosphonium-based ionic liquids for separating H2S and CO2 from natural gas: insights from molecular dynamics simulation - Umar Muhammad Yahaya; Hossein Haghani; Jun Xia; Luciano T. Costa; Teerawat Sema (Results in Engineering)
Sour natural gas contains significant amounts of H2S, CO2, and other sulfur-containing components. In this work, we conducted molecular dynamics (MD) simulations of five phosphonium-based ionic liquids (PILs) with a gas mixture (GM) containing 80 % CH4, 10 % CO2, 5 % H2S, and 5 % N2, reflecting a typical sour natural gas composition. Simulation was performed at 300 K and 50 bar. Five PILs are [P4444][ACE], [P4444][FOR], P4444][MTC], [P4444][DMP], and [P4444][DEP]. Analysis of radial distribution functions indicated that PILs have a higher affinity and absorption capacity to acid gases over CH4. Among the simulated PIL+GM systems, [P4444][FOR]+GM has the highest absolute value of the negative electrostatic energy (47,564.2 kJ mol−1) and the lowest absolute value of the negative van der Waals energy (21,447.8 kJ mol−1). As a result, [P4444][FOR] has the lowest CH4 absorption capacity of 0.128 mol/mol and the highest acid gas selectivity of 7.750 mol/mol and 9.523 mol/mol for CO2 and H2S, respectively. [P4444][ACE] has the best acid gas absorption capacity of 1.181 mol/mol for CO2 and 1.373 mol/mol for H2S. This showed that a carboxylate functional group enhances acid gas absorption capacity while the higher electrostatic energy favors their selectivity. The self-diffusivity of CH4 in the PILs is higher than that of CO2 or H2S. This manifested an unfavorable interaction between PILs and CH4, leading to its low absorption capacity. This study demonstrated that PILs with a carboxylate functional group on the anion are preferable over those with phosphate in formulating sour gas sweetening absorbents.